HUBUNGAN PENGETAHUAN ANTI KORUPSI DENGAN PERILAKU NILAI-NILAI ANTI KORUPSI PADA MAHASISWA - Satria Pinandhita; Suci Utami; Adi Irwansyah (Lembaga Penelitian & Pengabdian Masyarakat Sekolah Tinggi Ilmu KesehatanBrebes, 2021)
Background: Commitment to eradicating corruption is very important in government in a country. KPK has a focus on the health sector. There are two aspects that may become fields of corruption in the Health sector, namely Health Infrastructure and disease prevention efforts such as procurement of health equipment and medicines. This makes it important to prevent acts of corruption that need to be carried out through the Education sector for students of Health Study Program. The purpose of this study was to determine the relationship between anti-corruption knowledge and anti-corruption value behavior in students at STIKes Brebes in 2021. Methods: The type of research conducted was analytic. With a correlational research design. As the research population, there are 142 students of STIKes Brebes. Data was collected using primary data with univariate and bivariate data analysis and then analyzed by Chi-square statistical test. Results: The results showed that 49.3% of students had good knowledge, 46.5% had sufficient knowledge, 99.4% of students had positive attitudes about anti-corruption values. Based on the results of the chi square statistical test about the relationship with knowledge, the p value obtained is 0.003, so the conclusion is Ha is accepted and Ho is rejected, which means there is a relationship between knowledge and anti-corruption value behavior. Conclusion: students' knowledge about anti-corruption is 49.3% good and 46.5 enough. The anti-corruption values ​​of 94.4% students have positive behavior, and there is a significant relationship between anti-corruption knowledge and anti-corruption value behavior in students at STIKes Brebes.